2009
DOI: 10.1037/a0015334
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal theta-band activity and trace eyeblink conditioning in rabbits.

Abstract: We aimed to examine the relationship between hippocampal theta activity and trace eyeblink conditioning. Hippocampal electrophysiological local field potentials were recorded before, during, and after conditioning or explicitly unpaired training sessions in adult male New Zealand White rabbits. As expected, a high relative power of theta activity (theta ratio) in the hippocampus predicted faster acquisition of the conditioned response during trace conditioning, but, contrary to previous results obtained using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…High-amplitude, well phase-locked hippocampal fissure u-band responses to the conditioned stimulus early in training predicted better learning of trace eyeblink conditioning Previous studies indicate a correlation between hippocampal function and learning only, or at least especially, early in training (Nokia et al 2009). To study the link between hippocampal uband responses and learning, we calculated correlations between the relative amplitude/phase-locking of hippocampal u-band responses to the CS during the first conditioning session and the percentage of CRs elicited during conditioning (blocks 1 -8).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…High-amplitude, well phase-locked hippocampal fissure u-band responses to the conditioned stimulus early in training predicted better learning of trace eyeblink conditioning Previous studies indicate a correlation between hippocampal function and learning only, or at least especially, early in training (Nokia et al 2009). To study the link between hippocampal uband responses and learning, we calculated correlations between the relative amplitude/phase-locking of hippocampal u-band responses to the CS during the first conditioning session and the percentage of CRs elicited during conditioning (blocks 1 -8).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicate that the spontaneous level of hippocampal u activity predicts subsequent learning (Berry and Thompson 1978;Nokia et al 2009). Thus, to ensure there was no underlying difference in baseline u between the Peak and the Trough groups, data from a 5-min stimulus-free recording conducted immediately before the first conditioning session were analyzed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, CS-evoked theta-band phase locking (Siegel et al, 2009) and theta oscillation in general (Nokia et al, 2009) have been shown to strengthen immediately preceding the onset of CR acquisition in the course of trace eyeblink conditioning. At the neuronal level, phase locking of neural oscillations within a structure, as well as synchronized oscillations between functionally related brain structures, allows predictability in terms of neuronal communication.…”
Section: Discussionmentioning
confidence: 99%